Instilling social and personal values in early childhood through reading-based activities - HODA, Abuo Afash (Acta et Commentationes, Sciences of Education, 2025)
This study explores how children’s literature contributes to instilling social and personal values in early childhood. Conducted within Arab society in Israel, the research compares methodologies of developing values over three years: one that combined story reading with follow-up activities and another that focused solely on reading. Using a mixed quantitative–qualitative approach (Schwartz Value Questionnaire and interviews), it examined how 30 stories influenced value formation and reading development. Findings show that integrating post-reading activities significantly enhances both value acquisition and reading comprehension. The most emphasized values were acceptance of others, love, respect, responsibility, and identity. The study highlights the educational potential of literature-based experiential learning in early childhood.